Stress calculation method of bending multilayer structural element when bending moment acts in the planes that do not coincident with principal planes - Kleiza , Vytautas; Kleiza, Jonas (Lietuvos matematikos rinkinys, 2021)
This paper presents stress calculationmethod of bending multilayer structural element when bending moment acts in the planes that do not coincident with principal planes, and cross section is symmetric or asymmetric. Carrying the computation of occurring stress values in multilayer beam layers it is necessary to identify coordinates of cross-section stiffness centre, direction of principal axes, and coordinates of specific points regarding principal axes. Having this information and equation which is valid for stress calculation of bending multilayer beams it is possible to identify normal stress values at any point of the beam cross section under skew bending. It is deduced that stress values and the nature of their changes are influenced by the shape of beam cross-section, its asymmetry degree, and the direction of appliedmoment.
Keywords: multilayer beam; bending stiffness; skew bending